The Effects of the Organizational Justice on the Well-Being of Employees in Surabaya - Marvin Christian Prayogo (iBuss Management, 2019)
In 2018, Cigna Indonesia performed a survey of over 1000 Indonesian employees, as part of its parent company’s global Well-Being 360° Survey. Results of the survey found a 75% stress-approval percentage amongst its Indonesian respondents – the lowest statistic amongst the rest of the participant countries, of which averaged to an 86% approval rate. For comparison, Singapore was appointed a staggering 91% approval rate amongst its employee respondents. Considering Indonesia’s unimpressive standings in the global scale, the lack of proper, published researches on employee well-being in Indonesia shines Cigna’s aforementioned statistics as deviation from the norm- an anomaly, so to speak, begging for explanation.As a concept in workplace literature, employee well-being refers to the quality of an employee’s overall psychological, physical, and social experience in the workplace. This paper will peer through employee well-being through the lens of organizational justice theory.Acting as a positivistic, quantitative study, this paper uses distributed questionnaires answered by at 118 respondents as its research instrument of choice. The subjects of the study are employees in Surabaya. Results of the questionnaire was processed using the Multiple Linear Regression Analyses, namely the Adjusted R-square test, the F-test, and the t-test. The research concluded that organizational justice had an insignificant influence towards the well-being of respondents. Keywords: Organizational Justice; Job strain; Effort-reward imbalance; Employee well-being; Indonesia